The Effect of Servitization on Purchase Intention Using Digital Technology and Service Business Focus as Mediating Variable - Akhmad, Dati Putra Nur; Sidiq Permono Nugroho (Manunggal Halim Jaya, 2025)
The development of digital technology has changed the business landscape significantly, especially in terms of improving operational efficiency and customer experience. One strategy that companies are increasingly implementing is servitization, namely a shift from a product-based business model to a service that provides added value for customers. This study aims to analyze the influence of servitization on purchase intention and the role of digital technology and service business focus as mediators in this relationship. This research uses quantitative methods with data collection techniques through questionnaires distributed to 75 respondents consisting of coffee shops and restaurant businesses in Solo Raya. Data analysis was carried out using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 3.0 software. The research results show that servitization positively and significantly affects purchase intention, digital technology, and service business focus. However, digital technology does not directly influence purchase intention, indicating that digital technology alone is insufficient to increase customer purchase intention without an appropriate service strategy. Meanwhile, service business focus has been proven to significantly influence purchase intention and mediate the relationship between servitization and purchase intention. These findings confirm that companies that implement servitization and have a strong focus on business services are better able to increase customer purchasing intentions than relying solely on digital technology. Therefore, companies are advised to adopt digital technologies and ensure that their service strategies can increase customer value.